Developing cancer vaccine with carcinoembryonic antigen and IGF-1R as immunostimulants using immunoinformatics approach - Ezediuno, Louis O (Korean Society of Surgical Oncology, 2026)
Purpose
Colorectal cancer (CRC) remains a significant global health burden, necessitating innovative approaches for prevention and treatment. This study proposes a multiepitope vaccine targeting carcinoembryonic antigen (CEA) and insulin-like growth factor-1 receptor (IGF-1R), two prominent biomarkers associated with CRC progression.
Methods
Sequences of CEA and IGF-1R proteins were retrieved from NCBI databank, the sequences were aligned on the MEGA5 tool to identify conserved regions. Immunological and structural predictive analysis which include antigenic potential prediction, cytotoxic T-lymphocytes (CTLs), helper-T lymphocytes (HTLs), B-cell epitopes predictions, and prediction of the vaccine secondary and tertiary structure were performed. The vaccine was evaluated to validate its physiochemical and immunological properties. To determine the binding energy and domain, the tertiary structure of the vaccine was docked to Toll-like receptor 4, and viewed on PyMOL and LigPlot+ tools.
Results
CEA and IGF-1R were revealed to be highly antigenic, and non-allergens demonstrating the capacity to elicit robust immune responses, which include CTLs, HTLs, and B cells activation. The secondary structure revealed a conformation closely resembling native protein, with alpha helices, beta sheets, and coils, indicative of favorable interactions. Tertiary structure prediction predicted five models, model 0 was selected and validated due its highest confidence, and validation revealed that 87.5% of residues were within favored regions, with a z-score of 4.03. Molecular docking predicted strong binding complex with low binding energy.
Conclusion
Based on our analysis, the proposed multiepitope vaccine holds promise as an effective preventive measure against colorectal cancer development.